Parliamentary inviolability does not cover disobeying the Constitutional Court (comment to STC 184/2021, of October 28) - José Ignacio (Journal of the Basque Parliament, 2022)
In this ruling, the Constitutional Court analyzes the constitutional legitimacy of the actions of Mrs. Forcadell, who was criminally convicted due to her participation as President of the Parliament of Catalonia in certain parliamentary actions to promote the so-called procés. The arguments of the High Constitutional Interpreter are relevant in this judgment regarding the inadmissibility of alleging the parliamentary prerogative of inviolability as a justifying argument for an attitude reluctant to comply with the requirements of that Court in order not to process certain parliamentary initiatives within the framework of the Catalan independence process.
Keywords: parliamentary prerogatives; inviolability; disobedience